Recombinant activated factor VII for refractory bleeding during pediatric spinal tumor surgery: A case report (Indian Journal of Case Reports, 2018)
Bleeding complications constitute a particular challenge in neurosurgical procedures especially in children and may be life-threatening. We report the case of a 5-month-old boy to whom recombinant activated factor VII was given at doses of 90 ?g/kg of body weight for the control of refractory perioperative bleeding during spinal neurofibromas surgery. Conventional treatment with fresh-frozen plasma, platelet concentrates, and fibrinogen concentrate failed to control hemorrhage. Recombinant activated factor administration resulted in decreased bleeding, hemodynamic stabilization, and improved surgical hemostasis.